2009
DOI: 10.1002/chem.200900856
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐ or Platinum‐Catalyzed Cascade Processes of Alkynol Derivatives Involving Hydroalkoxylation Reactions Followed by Prins‐Type Cyclizations

Abstract: An efficient method for the synthesis of [3.3.1]bicyclic compounds from easily available alkynol derivatives has been developed. The reaction is based on a gold- or platinum-catalyzed tandem process that involves an intramolecular hydroalkoxylation of a triple bond followed by a Prins-type cyclization. The reaction has been carried out with differently substituted alkynol derivatives and oxygen-, nitrogen-, and carbon-centered nucleophiles. The incorporation of halogen atoms as nucleophiles and elimination rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 99 publications
0
31
0
Order By: Relevance
“… 97 Shortly later, a gold(I)-catalyzed tandem intramolecular hydroalkoxylation/Prins-type cyclization was described, affording oxygen-containing [3.3.2] bicyclic compounds 58 diastereoselectively (Scheme 20 ). 98 …”
Section: Addition Of Heteronucleophiles To Alkynesmentioning
confidence: 99%
“… 97 Shortly later, a gold(I)-catalyzed tandem intramolecular hydroalkoxylation/Prins-type cyclization was described, affording oxygen-containing [3.3.2] bicyclic compounds 58 diastereoselectively (Scheme 20 ). 98 …”
Section: Addition Of Heteronucleophiles To Alkynesmentioning
confidence: 99%
“…PG = protecting group. In addition, amides containing different substituents on the indole ring also underwent smooth cascade cyclization,p roducing the corresponding 2f-n in good to excellent yields (entries [6][7][8][9][10][11][12][13][14], Finally,i tw as found that the reaction also occurred well with (S)-(+ +)-tert-butylsulfinamide-derived 1e' ',a nd thus the other enatiomer, 2e' ', was specifically produced (entry 15). Further screening of solvents such as toluene and chlorobenzene led to as lightly decreased yield (entries [14][15].…”
Section: Resultsmentioning
confidence: 99%
“…for the synthesis of [3.2.1]bicyclic acetals, and notable is that endo ‐hydroalkoxylation was observed in case of internal akynes . In 2006, Barluenga and co‐workers reported an outstanding protocol for either the gold‐ or platinum‐catalyzed tandem exo ‐hydroalkoxylation/Prins‐type cyclization, leading to a variety of 9‐oxabicyclo[3.3.1]nonanes (Scheme c) . On the basis of this work, the relevant tandem exo ‐hydroalkoxylation/hydroarylation was further developed by the same group .…”
Section: Introductionmentioning
confidence: 88%
“…[7] Following this concept, transition-metalcatalyzed alkyne hydroalkoxylation-and hydroaminationinitiated cascade cyclizations have been well documented to be ap owerful method to synthesize av ariety of structurally complex heterocycles, [4] especially the valuable bridged heterocycles. [8][9][10][11] Fore xample,M ichelet and Genẽ tr eported in 2005 ag old-catalyzed tandem exo-hydroalkoxylation/ hydroalkoxylation of bis-homopropargylic diols,a llowing the facile formation of functionalized strained bicyclick etals (Scheme 1b). [8a] Ar elated platinum-catalyzed tandem cycloisomerization of alkyne diols was subsequently disclosed by Ley et al for the synthesis of [3.2.1]bicyclic acetals,a nd notable is that endo-hydroalkoxylation was observed in case of internal akynes.…”
Section: Introductionmentioning
confidence: 99%